2011
DOI: 10.1590/s1413-86702011000100017
|View full text |Cite
|
Sign up to set email alerts
|

Pegylated interferon/ribavirin-associated sudden hearing loss in a patient with chronic hepatitis C in Brazil

Abstract: Sudden hearing loss is defined as a sensorineural hearing loss, equal to or greater than 30 dB, at three or more consecutive frequencies, which takes place within 72 hours. Both peginterferon and ribavirin are well-known to be associated with significant adverse effects, but sudden hearing loss is uncommon. We report a 65-year-old male patient who developed sudden-onset hearing loss during combination therapy with pegylated interferon-alpha and ribavirin for chronic hepatitis C. Peginterferon and ribavirin may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Our review identified nine separate case reports of severe sudden hearing loss in patients receiving pegylated (PEG)‐IFN/ribavirin combination therapy. Of these, unilateral SNHL was far more common, occurring in eight out of the nine patients 12–19 . Three cases reported temporary hearing loss that improved with cessation of pegylated (PEG)‐IFN/ribavirin combination therapy 13,14,18 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our review identified nine separate case reports of severe sudden hearing loss in patients receiving pegylated (PEG)‐IFN/ribavirin combination therapy. Of these, unilateral SNHL was far more common, occurring in eight out of the nine patients 12–19 . Three cases reported temporary hearing loss that improved with cessation of pegylated (PEG)‐IFN/ribavirin combination therapy 13,14,18 .…”
Section: Resultsmentioning
confidence: 99%
“…Three cases reported temporary hearing loss that improved with cessation of pegylated (PEG)‐IFN/ribavirin combination therapy 13,14,18 . SNHL was fully reversible in two cases (after prednisone treatment) and permanent in four cases, even after cessation of treatment 12,15–17,19,20 . Tinnitus occurred concurrently with hearing loss in one case 16 …”
Section: Resultsmentioning
confidence: 99%